Social anxiety and emotional maladaptation in adolescence (The Journal of Psychology and Sociology, 2021)
Social anxiety is reflected in all areas of a teenager’s life. Negative symptoms, such as a decrease in the child’s mood, a violation of emotional relations with family and a deterioration in relations with friends, and a decrease in academic performance, indicate the presence of pronounced emotional mal- adaptation. The article describes modern approaches and theories to study the relationship between so- cial anxiety and emotional maladaptation in adolescents. In order to determine the relationship between social anxiety and emotional maladaptation, the “social avoidance and distress scale” (SADS, Watson D., Friend R., 1969; validization-Krasnova, 2013), “a short scale of fear of negative evaluation” (Fear of Negative Evaluation, FNE, Watson D., Friend R., 1969) and M. Kovac’s “questionnaire for determin- ing depression in children” (M. Kovacs. , 1992., validization - Volikova, Kalina, Kholmogorova, 2011) questionnaires were conducted on 56 samples, of which 6% showed a high level of social anxiety. It was concluded that the level of social anxiety in students of grades 8-9 is higher than in grades 6-7. It was found that there is a link between the general indicator of social anxiety (social isolation and social distress) and suicidal thoughts (M. Kovak’s questionnaire for determining depression in children, scale e). That is, according to our hypothesis, as the level of social anxiety increases, suicidal thoughts, symptoms of depression and signs of emotional maladaptation become more pronounced in a teenager.Key words: social anxiety, emotional maladaptation, adolescence, social phobia, social isolation.